Knowledge visualization and mapping of information literacy, 1975–2018. (June 2020) - Onyancha, Omwoyo Bosire
This article examines the evolution of information literacy over 43 years (from 1975 to 2018), using knowledge visualization and mapping of its literature, as indexed in the Scopus database. Results reveal that information literacy has evolved from being a library- and/or librarianship-oriented concept to a multidisciplinary field and is no longer restricted to social sciences but is spread across 27 disciplines in Scopus' subject classification. New literacies have emerged after 2000 to include digital literacy, media literacy, health literacy, business information literacy, metaliteracy, content literacy, workplace information literacy, scientific literacy and science literacy. Library instruction remains a prominent method of information literacy delivery in academic libraries. We conclude that information literacy is dynamic and spread across many disciplines and would, therefore, require interdisciplinary and collaborative approaches for its effective delivery in what is turning out to be diverse and complex information and learning environments.